The Influence of Teachers’ Metacognitive Skills and Classroom Management On Students’ Learning Motivation at SMA Negeri 2 Beo, Talaud Islands Regency - Jurni Pande; Jefry Sony Junus Lengkong; Mozes M. Wullur; Romi J. Mongdong (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of teachers’ metacognitive skills and classroom management on students’ learning motivation at SMA Negeri 2 Beo. The main issues underlying this research are low student participation, lack of concentration during learning activities, and minimal initiative in completing academic tasks. The study employed a quantitative method with a survey approach involving 30 respondents selected through Proportional Random Sampling from a total population of 88 students. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The partial test results (t-test) indicate that teachers’ metacognitive skills have a significant effect on learning motivation, with a t-value of 3.653 > t-table of 2.052 (sig. 0.001). Similarly, classroom management shows a significant effect, with a t-value of 4.876 > t-table of 2.052 (sig. 0.019). Simultaneously (F-test), both variables significantly influence learning motivation, with an F-value of 8.252 > F-table of 3.35 (sig. 0.002). The coefficient of determination (R Square) of 0.679 indicates that these two variables contribute 67.9% to the variance in students’ learning motivation. In conclusion, teachers’ ability to plan and evaluate their own thinking processes (metacognition), combined with effective classroom management strategies, is a crucial factor in enhancing students’ learning motivation. Schools are recommended to provide continuous training for teachers to optimize these competencies.